2004
DOI: 10.1007/s00240-004-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sustained and local administration of epidermal growth factor on improving bilateral testicular tissue after torsion

Abstract: Epidermal growth factor (EGF) modulates Leydig cell proliferation, steroidogenesis, spermiogenesis, and Sertoli cell activity. It plays an important role in repairing ischemia-reperfusion injury in different tissues. The aim of this study was to evaluate the effects of sustained and local administration of EGF on improving bilateral testicular tissue after torsion. A total of 57 Wistar albino rats were used. For the EGF transport system, 1x2 cm gelatin films containing 2 microg EGF were used. Torsion was creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 42 publications
7
42
4
Order By: Relevance
“…In the present study, the lowest MTBS values in testes were found in diabetic group. Another histoAktas et al pathological criterion of testicular damage used in the present study was the MSTD value, which is also used in the scientific literature to estimate testicular tissue damage (Uguralp et al, 2004). In the present study, the lowest MSTD value was also observed in diabetic group, which is similar to results obtained for MTBS values and is in accordance with previous studies (Altay et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the lowest MTBS values in testes were found in diabetic group. Another histoAktas et al pathological criterion of testicular damage used in the present study was the MSTD value, which is also used in the scientific literature to estimate testicular tissue damage (Uguralp et al, 2004). In the present study, the lowest MSTD value was also observed in diabetic group, which is similar to results obtained for MTBS values and is in accordance with previous studies (Altay et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…It is based on the evaluation of progressive degeneration of the germinal epithelium (Johnsen, 1970;Uguralp et al, 2004). In the present study, the lowest MTBS values in testes were found in diabetic group.…”
Section: Discussionsupporting
confidence: 45%
“…EGF significantly protects against intestinal IR injury. Sustained administration of EGF after testicular torsion improves bilateral testicular injury (Uguralp et al 2004). Moreover, emerging evidences demonstrated that EGF signaling is able to decrease ROS production, which has been suggested to play an important role during IR pathogenesis, in the intestine, pancreas, and renal tissue (Maeda et al 2004, Hussein Ael et al 2011.…”
Section: Role Of Egf In Testicular Ischemia-reperfusion Injurymentioning
confidence: 99%
“…The EGF-GF ligands, EGF, transforming growth factor-a, and b-cellulin stimulate DNA synthesis in microdissected stage I segments of rat testis seminiferous tubules in vitro (Wahab-Wahlgren et al 2003). More recently, it has been shown that supplement of exogenous EGF after testicular torsion improves bilateral testicular injury (Uguralp et al 2004). Given the anti-apoptotic/ proapoptotic effect of EGF signaling is highly dose dependent (usually low concentrations of EGF promoted proliferation, while high concentrations of EGF induced cell cycle arrest, inhibition of proliferation, and apoptosis) (Zhao et al 2006), we hypothesize that the endogenous EGF may play an important role during the pathogenesis of testicular IR injury.…”
Section: Introductionmentioning
confidence: 99%
“…Although the EGF receptors in spermatozoa of several mammalian species have been demonstrated (Naz and Minhas 1995), the role of EGF in sperm function regulation is not ascertained (Oliva-Hernandez and Perez-Gutierrez 2008). Lack of EGF in plasma of mouse males led to the decrease in sperm concentration and motility (Liu et al 1994), whilst the administration of exogenous EGF was useful for repair of testicular disorders (Uguralp et al 2004;Kurokawa et al 2005) or for the treatment of male infertility in rodents (Cheng et al 2006). EGF regulates sperm functions (capacitation, acrosome reaction) through the activation of tyrosine kinase (Furuya et al 1993a;Naz and Kaplan 1993) or protein kinase C (Lax et al 1994), which are activated by specific EGF receptors demonstrated in several animal species (Naz and Ahmad 1992;Naz and Minhas 1995;Oliva-Hernandez and Perez-Gutierrez 2008).…”
Section: Introductionmentioning
confidence: 99%